Do factor shares reflect technology? - Benjamin Bental; Dominique M. Demougin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This note demonstrates that it is easily possible to compute technological parameters out ot national income acconting data in the presence of bargaining in the labor market. Applying the method to US data, we obtain that the output elasticity with respect to capital exceed 0.5.
Keywords: E23; E25; 330; Factor shares; Nash bargaining